A comparison of UV-induction in exponentially growing and resting Escherichia coli B/r Hcr+ - Slezáriková, V; Sedliaková, M (Folia microbiologica, 1979)
Using the method of two separate UV exposures the increase of UV resistance after various induction fluences in growing and resting Escherichia coli B/r Hcr+ was followed. In resting cells, the optimum induction energy fluence was found to be 30 J/m2. In exponentially growing cells testing of induction has proved to be possible only under conditions of postincubation of cells with chloramphenicol after the second fluence. Under these conditions the induction energy fluence up to the observed 50 J/m2 resulted in an increased survival.
Keywords: Chloramphenicol; chloramfenikol; Radiation Dosage; Ultraviolet Rays; Escherichia coli; dávka záření; ultrafialové záření